Comparison of the Efficacy of ShuoTong Ureteroscopy and Simple Flexible Ureteroscopy in the Treatment of Unilateral Upper Ureteral Calculi - Lai, Longhui; Zhang, Wenzhao; Zheng, Fangjian; Wang, Tao; Bai, Peide; Liu, Zhengsheng; Zheng, Jiaxin; Shao, Zhiqiang; Duan, Bo; Wang, Huiqiang; Xing, Jinchun; Chen, Huixin; et al. (Frontiers in Surgery, 2021)
Background: ShuoTong ureteroscopy (Sotn-ureteroscopy, ST-URS), a new lithotripsy operation method developed on the basis of ureteroscopy, is widely used to treat ureteral stones in China. Its composition includes rigid ureteral access sheath, standard mirror, lithotripsy mirror, and ShuoTong perfusion aspirator (ST-APM). Here, we compared the efficacy and safety of the ST-URS and the flexible ureteroscope (F-URS) holmium laser lithotripsy in the treatment of unilateral upper ureteral calculi. Methods: Retrospective analysis was conducted on the clinical data of 280 patients who met the inclusion 1) urinary tract CT was diagnosed with unilateral single upper ureteral calculi above the L4 lumbar spine; 2) patient age was from 18 to 80 years old; 3) patients were informed and consented to this study; and 4) patients were approved by the hospital ethics committee (proof number: KY-2019-020) and the exclusion criteria for unilateral upper ureteral calculi in the First Affiliated Hospital of Xiamen University from January 2018 to November 2020, and they were divided into the ST-URS group and the flexible ureteroscopy (F-URS) group. Results: The stone-free rate of 1 day after operation of the ST-URS group was significantly higher than the F-URS group (63.71 vs. 34.62%, P < 0.0001). The operative time (38.45 vs. 46.18 min, P = 0.005) and hospitalization cost (27,203 vs. 33,220 Yuan, P < 0.0001) of the ST-URS group were significantly lower than the F-URS group. There were no significant differences in the success rate of ureteral access sheath placement, operative blood loss, stone-free rate of 1 month after operation, postoperative complications, postoperative hospital stay, and postoperative visual analog scale (VAS) pain score between the two groups (P > 0.05). In subgroups of a diameter of calculi ≥ 1.5 cm, calculi CT numerical value ≥ 1,000 Hounsfield unit and the preoperative hydronephrosis range ≥ 3.0 cm, ST-URS shows more advantages in the operative time, stone-free rate of 1 day after the operation, the hospitalization cost, and the incidence of postoperative complications. Conclusion: In unilateral upper ureteral stones treated with a holmium laser, compared with the simple F-URS, the ST-URS has a shorter operative time, lower hospitalization cost, and a higher stone-free rate of 1 day after the operation, suggesting that the ST-URS could be more widely applied in clinics.